2020
DOI: 10.1111/acel.13108
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin loss as a determinant of progerin‐induced DNA damage in Hutchinson–Gilford Progeria

Abstract: Hutchinson–Gilford progeria is a premature aging syndrome caused by a truncated form of lamin A called progerin. Progerin expression results in a variety of cellular defects including heterochromatin loss, DNA damage, impaired proliferation and premature senescence. It remains unclear how these different progerin‐induced phenotypes are temporally and mechanistically linked. To address these questions, we use a doxycycline‐inducible system to restrict progerin expression to different stages of the cell cycle. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 46 publications
3
47
0
Order By: Relevance
“…The combined effects of these changes in chromatin result in altered gene expression [39,42]. Recently, Dreesen and coworkers reported that progerin-dependent heterochromatin loss is a rapid and dynamic process [43]. This loss can be reversed, as progerin removal restores heterochromatin levels and results in no permanent DNA damage or proliferation defect.…”
Section: What Is the Cellular Impact Of A Defective Prelamin A Procesmentioning
confidence: 99%
“…The combined effects of these changes in chromatin result in altered gene expression [39,42]. Recently, Dreesen and coworkers reported that progerin-dependent heterochromatin loss is a rapid and dynamic process [43]. This loss can be reversed, as progerin removal restores heterochromatin levels and results in no permanent DNA damage or proliferation defect.…”
Section: What Is the Cellular Impact Of A Defective Prelamin A Procesmentioning
confidence: 99%
“…Similar to chronologically aged normal human cell, progeric cells exhibit loss of transcriptionally repressed and compacted peripheral heterochromatin, as shown by a reduction in histone H3 trimethylation at lysines 9 and 27 (H3K9me3 and H3K27me3) and electron microscopy [23,36,47,48]. Loss of heterochromatin is concomitant with the down-regulation of many proteins involved in epigenetic silencing, including the Enhancer of zeste homolog (EZH2), a member of the polycomb repressive complex (PRC) 2, heterochromatin protein 1 homolog-α (HP1α) and the histone N-methyltransferase Suppressor of variegation 3-9 homolog 1 (SUV39H1) [37,47,49].…”
Section: Loss Of Peripheral Heterochromatinmentioning
confidence: 96%
“…What is clear is that progerin-induced heterochromatin loss is not a consequence of cells undergoing senescence; as an expression of progerin in immortalized, or telomerase-positive cells, did not prevent heterochromatin decompaction [23,36]. Furthermore, by expressing progerin during different cell cycle stages, it was recently shown that progerin triggers heterochromatin decompaction in growth-arrested (G0) cells, whilst DNA damage accumulates exclusively during DNA replication, thus separating these two phenotypes [48]. By visualizing heterochromatin levels (H3K9me3 and H3K27me3), DNA damage and progerin levels at single-cell resolution, it was also shown that cells with low levels of heterochromatin are more prone to accumulate progerin-induced DNA damage, whilst progerin removal (in G0 cells) restored heterochromatin levels and prevented DNA damage accumulation during subsequent rounds of DNA replication [48,53].…”
Section: Loss Of Peripheral Heterochromatinmentioning
confidence: 99%
See 1 more Smart Citation
“…Another consequence of progerin accumulation and lamina thickening is the loss of heterochromatin, LAD structure and gene repression [70][71][72] as a result of lost lamina interactions with epigenetic regulators, such as DNA methyl transferases (DNMT1 [73,74]) and histone methyltransferases (such as EZH2 [71,75]). Chojnowski and colleagues propose that the initial loss of heterochromatin due to progerin accumulation [76] predisposes HGPS cells to other downstream defects such as DNA damage while removal of progerin results in heterochromatin reformation.…”
Section: Hutchinson-gilford Progeria Syndrome (Hgps): a Protein Accummentioning
confidence: 99%